A case report of proctitis associated with Mycoplasma genitalium in a man who has sex with men. (May 2019) - Isabel Lázaro-Simó, Anna; Esperalba-Esquerra, Juliana; Vall-Mayans, Martí
Mycoplasma genitalium is an infection of increasing concern due to its potential to cause sequelae in the reproductive tract and the development of antimicrobial resistance. Its role as a cause of proctitis in people with high-risk sexual behaviour has not been properly defined yet but it seems to be less symptomatic than proctitis caused by Chlamydia trachomatis or Neisseria gonorrhoeae . We present a case of a man who has sex with men with proctitis associated with M. genitalium after excluding other infections known to cause STI proctitis.